Review of the Flexible Credit Line and Precautionary Credit Line. (Policy Papers; Policy Paper, 2011)
With the creation of the Flexible Credit Line (FCL) and Precautionary Credit Line (PCL), the Fund's GRA toolkit was overhauled to address gaps in the Fund's crisis prevention and resolution toolkit. The innovative and flexible nature of the new instruments was meant to reduce stigma from using Fund resources, underpinning confidence in its users amid stressed market conditions. Yet, there have been a limited number of members with these Using a variety of methodological tools, this review assesses experience with the instruments, arrangements. Using a variety of methodological tools, this review assesses experience with the instruments, reflects on the appropriateness of their design, and recommends refinements to enhance their effectiveness.